REPRESENTASI KEARIFAN LOKAL PADA LUKISAN BOROBUDUR DAN BEDAYA KETAWANG, KARYA SRIHADI SOEDARSONO - Dewi, Citra Smara (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
This study is based on representation of the values of local wisdom contained in the paintings Srihadi Sudarsono, especially on two phenomenal works that much as source of inspiration, namely Borobudur and Dance Bedaya Ketawang. The objective of this research is to identify the dimensions of the values of the local wisdom contained in the Srihadi Soedarsono’s paintings. This research is a qualitative research using literature review and analyzed descriptively with explorative approach. The results showed that: (1) an artist's social background with a very strong culture will affect the artistic process which is seen at the works of art produced (2) Representation of local values contained in the Srihadi’s paintings, representing the concept of representation, either individually or in groups, (3) The values of local wisdom in Srihadi’s paintings have values of local knowledge , local values and the local solidarity group dimensions.